2015
DOI: 10.1088/1475-7516/2015/05/037
|View full text |Cite
|
Sign up to set email alerts
|

Galvano-rotational effect induced by electroweak interactions in pulsars

Abstract: We study electroweakly interacting particles in rotating matter. The existence of the electric current along the axis of the matter rotation is predicted in this system. This new galvano-rotational effect is caused by the parity violating interaction between massless charged particles in the rotating matter. We start with the exact solution of the Dirac equation for a fermion involved in the electroweak interaction in the rotating frame. This equation includes the noninertial effects. Then, using the obtained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…In search of such an effect, we thus take b µ = (b, 0) in the rest frame of the nucleus and assume b to be small. Note that similar effects, having to do with mixing of electric and magnetic observables, have been discussed recently to appear in core-collapse supernovae, Weyl semimetals, and heavy-ion collisions [7][8][9].…”
Section: Introductionsupporting
confidence: 55%
“…In search of such an effect, we thus take b µ = (b, 0) in the rest frame of the nucleus and assume b to be small. Note that similar effects, having to do with mixing of electric and magnetic observables, have been discussed recently to appear in core-collapse supernovae, Weyl semimetals, and heavy-ion collisions [7][8][9].…”
Section: Introductionsupporting
confidence: 55%
“…The explicit form of these coefficients can be found analogously to Ref. [13]. Then, accounting for the chosen number densities of quarks in QS, n q = n 0 /3, we get that V 5u = 1.1 eV and V 5d = 4.1 eV.…”
Section: Introductionmentioning
confidence: 68%
“…The explicit expression for V 5q in ud quark matter was found in Ref. [13]. It is proportional to the number densities of quarks,…”
Section: Introductionmentioning
confidence: 99%
“…e w e × S e ; (31) in general, for a magnetised medium with magnetisation density M we can write the free current density j = ∇×B μ 0 − j M , where j M = ∇ × M is the magnetisation current density. Note that here we have discarded the displacement current term ∂ E ∂t .…”
Section: The Hydrodynamic Equationsmentioning
confidence: 99%
“…Though this assumption is justifiable for a core collapsing supernova, it is hard to satisfy in other scenarios like the early Universe. Electroweak plasma in a rotating matter is studied in [31]. In this work it is shown that the electric current can be induced in the direction of the rotation axis due to the parity violating nature of the interaction.…”
Section: Introductionmentioning
confidence: 99%